Outcomes of drug-eluting stents compared to bare-metal stents in ST-segment elevation acute myocardial infarction - João Brito; Manuel Almeida; Rui Campante Teles; Pedro Sousa; João Abecasis; Rita Calé; Pedro Gonçalves; Luís Raposo; Miguel Mendes (Revista Portuguesa de Cardiologia, 2011)
Introduction: Primary percutaneous coronary intervention (PPCI) has become the treatment of choice in patients with ST-segment elevation myocardial infarction (STEMI). Drug-eluting stents (DES) reduce restenosis compared to bare-metal stents (BMS) but there is conflicting data concerning their use in the setting of STEMI. We aimed to evaluate the influence of the type of stent on the outcomes of PPCI. Methods: This was a single-center longitudinal study including 213 consecutive patients (76% men, mean age 60±12 years) with STEMI undergoing PPCI between 2003 and 2007, divided into two groups: BMS (43.7%) and DES (56.3%). We assessed clinical and demographic features as well as angiographic and electrocardiographic signs of myocardial reperfusion. The composite outcome of death, myocardial infarction (MI) or target-lesion revascularization (TLR) was evaluated. Results: At a median follow-up of 26 months there were no differences in the composite outcome of death/MI/TLR (BMS 18.3% vs DES 15.8%) or in the incidence of stent thrombosis. Angiographic results of the procedure were also similar. Independent predictors of the composite outcome were age (HR=1.06, 95% CI [1.02-1.11], left anterior descending artery as infarct-related vessel (HR=2.69, 95% CI [1.17-6.19]) and use of glycoprotein IIb/IIIa inhibitors (HR=0.33, 95% CI [0.13-0.83]). Conclusions: There was no benefit in angiographic outcomes or major cardiac events after treatment with drug-eluting stents compared to bare-metal stents in this group of patients with STEMI. Resumo: Introdução: A angioplastia primária (ICPP) é o tratamento de eleição para enfarte agudo do miocárdio com elevação de ST (EAM ST). Os stents farmacológicos (DES) permitem reduzir a taxa de restenose coronária, sendo controverso o seu uso no contexto de EAM ST. O objectivo deste estudo foi avaliar os resultados clínicos da ICPP em função do tipo de stent usado (não revestido versus DES). População e métodos: Estudo longitudinal de centro único, incluindo 213 doentes consecutivos, idade média 60 ± 12 anos, 76% homens, submetidos a ICPP no contexto de EAM ST, entre 2003 e Novembro 2007. Foram considerados 2 grupos: stent não revestidos (BMS) (43,7%) e DES (56,3%). Analisaram-se as características clínicas e demográficas dos 2 grupos, comparando-se também variáveis angiográficas, de perfusão miocárdica, grau de resolução de segmento ST pós-ICPP e pico de troponina. Determinou-se no seguimento a incidência do evento combinado: morte, enfarte do miocárdio (EAM) ou revascularização de lesão alvo (TLR). Resultados: No seguimento mediano de 26 meses não se encontraram diferenças no evento combinado Morte/EAM/TLR (BMS 18,3% versus 15,8%) nem na trombose de stent. Os resultados angiográficos foram também semelhantes. Os preditores independentes de morte/EAM/TLR foram a frequência cardíaca (HR = 1.06 95% IC [1.02-1.11], descendente anterior como vaso culprit (HR = 2.69 95% IC [1.17-6.19]) e utilização de inibidores da glicoproteína IIbIIIa (HR = 0.33 95% IC [0.13-0.83]). Conclusão: O tipo de stent utilizado não parece ter influência na ocorrência de eventos cardíacos em doentes submetidos a angioplastia primária, no contexto de EAM ST. Keywords: Stents, Myocardial infarction, Percutaneous coronary intervention, Coronary disease/therapy, Palavras-chave: Stents, Enfarte do miocárdio, Intervenção coronária percutânea, Doença coronária/terapêutica